2021
DOI: 10.1002/mrd.23537
|View full text |Cite
|
Sign up to set email alerts
|

Metformin improves epigenetic modification involved in oocyte growth and embryo development in polycystic ovary syndrome mice model

Abstract: The possible relationship between dehydroepiandrosterone (DHEA)‐induced polycystic ovary syndrome (PCOS) and epigenetic changes (ECs) leading to the impaired oocyte quality, has not been investigated yet. So, this study aimed to provide an insight into the relationship of the impaired oocyte quality with ECs in a mice DHEA‐induced PCOS model and to further reveal the effect of metformin treatment. For this purpose, 80 female BALB/C mice were randomly divided into four equal groups, named as the control, sham, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…The epigenetic alterations induced by advanced maternal aging, mitochondrial dysfunctions, abnormal nutrition supply and abnormal expression levels of hormones trigger seriously meiotic defects of mammalian gametes, subsequently resulting in the incidence of aneuploidy after fertilization and embryonic development defects. 17 In consistent with our present study, these former literature have revealed that the promotion of epigenetic modifications via the amelioration of mitochondrial dysfunctions significantly improved the development potentials of mammalian oocytes, 16,17,[64][65][66] further addressing the future applications of Se/CDs as dietary supplementation in mammalian IVM via the promotion of epigenetic modifications. However, the specific regulation mechanism related to the effect of Se/CDs' supplementation in the epigenetic modifications of ovine MII oocytes and the potential effect of Se/CDs' supplementation on the epigenetic modifications of ovine zygote and/or blastocyst need more detailed investigations.…”
Section: Dovepresssupporting
confidence: 90%
“…The epigenetic alterations induced by advanced maternal aging, mitochondrial dysfunctions, abnormal nutrition supply and abnormal expression levels of hormones trigger seriously meiotic defects of mammalian gametes, subsequently resulting in the incidence of aneuploidy after fertilization and embryonic development defects. 17 In consistent with our present study, these former literature have revealed that the promotion of epigenetic modifications via the amelioration of mitochondrial dysfunctions significantly improved the development potentials of mammalian oocytes, 16,17,[64][65][66] further addressing the future applications of Se/CDs as dietary supplementation in mammalian IVM via the promotion of epigenetic modifications. However, the specific regulation mechanism related to the effect of Se/CDs' supplementation in the epigenetic modifications of ovine MII oocytes and the potential effect of Se/CDs' supplementation on the epigenetic modifications of ovine zygote and/or blastocyst need more detailed investigations.…”
Section: Dovepresssupporting
confidence: 90%
“…Previously published studies also summarized the effects of metformin on the epigenome, including epigenetic-modifying enzymes, histone and DNA methylation, and gene expression (Bridgeman et al 2018 ; Faure et al 2018 ). Consistent with our findings, a recent study showed that metformin could reduce oxidative stress and H3K9me3 in the oocytes of PCOS (Amani Abkenari et al 2021 ). Unlike the Trim-Away results of RIF1, the metformin intervention improved the DNA methylation status in addition to improving the histone modification.…”
Section: Discussionsupporting
confidence: 93%
“…In general, the treatment of the underlying reason of cytokine profile disruption is beneficial and may reverse the diseases' negative effects on fertilisation and pregnancy outcomes. A good example of this is PCOS, in which insulin resistance therapy, body weight reduction, and lifestyle changes, as well as pharmacological treatments, for example, metformin, can have a beneficial effect on the leptin levels and cytokine profile of patients [49][50][51].…”
Section: Practical Aspects and Unanswered Questionsmentioning
confidence: 99%